The replication protein of duck circovirus unwinds dsDNA in an ATP-driven and metal ion-dependent manner from 3′ to 5′ - Tao, Lihan; Wu, Chengcheng; Li, Na; Lin, Cui; Tan, Jia; Huang, Jianzhen (Frontiers in Veterinary Science, 2025)
Duck circovirus (DuCV) causes immunosuppression, co-infection and increased mortality in ducks, and the prevalence and infection rate of DuCV have risen in recent years, resulting in significant economic losses to the duck industry. Studying the mechanism of virus replication is particularly important for controlling DuCV infection. The replication protein (Rep) encoded by the DuCV genome is a highly conserved enzyme and plays key roles in viral replication, making it an ideal target for antiviral drugs. However, the biochemical characteristics of DuCV Rep were still unknown. Here, we utilized the prokaryotic expression system to express the Rep, and the protein was purified and identified. Then, Rep’s activities and their influencing factors were explored by a series of experiments in vitro. The results showed that Rep had the enzyme concentration-dependent ATPase and unwinding activities, and dual functions of Rep were both affected by the type and concentration of divalent metal ions. Moreover, Rep was able to use the energy generated from the hydrolysis of any nucleoside triphosphates (NTPs) to unwind double-stranded DNA (dsDNA). Analogs and hydrolysates were unable to replace ATP for Rep to exert the unwinding activity. We also found that the 3′-terminal single-strand extension (3′-overhang) of the substrate was indispensable for the unwinding activity of Rep. The results indicated that Rep had a 3′–5′ unwinding directionality, and Rep was capable of unwinding dsDNA with a 3′-overhang of not less than 1 nt. In addition, the efficiency of the Rep-catalyzed unwinding reaction increased with the increase of the length of the 3′-overhang, but slightly decreased with the increase of the length of the duplex region. In this study, we systematically characterized the dual activities of DuCV Rep, which was conducive to deeply understanding the molecular mechanism of Rep in regulating virus replication and the development of antiviral drugs.